2014
DOI: 10.1021/om500173j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Dimethylbis(2-pyridyl)borate Nickel(II) Complexes: Unimolecular Square-Planar to Square-Planar Rotation around Nickel(II)

Abstract: The syntheses of novel dimethylbis(2-pyridyl)borate nickel(II) complexes 4 and 6 are reported. These complexes were unambiguously characterized by X-ray analysis. In dichloromethane solvent, complex 4 undergoes a unique square-planar to square-planar rotation around the nickel(II) center, for which activation parameters of ΔH⧧ = 12.2(1) kcal mol–1 and ΔS⧧ = 0.8(5) eu were measured via NMR inversion recovery experiments. Complex 4 was also observed to isomerize via a relatively slow ring flip: ΔH⧧ = 15.0(2) kca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 70 publications
0
26
0
Order By: Relevance
“…The negative Δ S ‡ of activation for this reaction is particularly noteworthy and indicates an ordered transition state that is inconsistent with a rate-limiting ligand-dissociation event. This suggestion is further corroborated by the fact that the decomposition of 2 is not measurably affected by the addition of up to 8 equiv of free CNAr Mes2 (Table ) . Accordingly, the kinetic data for 2 indicate that β-Cl elimination may not require an in-plane, open coordination site in Group 10 metal polymerization systems.…”
mentioning
confidence: 58%
“…The negative Δ S ‡ of activation for this reaction is particularly noteworthy and indicates an ordered transition state that is inconsistent with a rate-limiting ligand-dissociation event. This suggestion is further corroborated by the fact that the decomposition of 2 is not measurably affected by the addition of up to 8 equiv of free CNAr Mes2 (Table ) . Accordingly, the kinetic data for 2 indicate that β-Cl elimination may not require an in-plane, open coordination site in Group 10 metal polymerization systems.…”
mentioning
confidence: 58%
“…(b) The σ-complex-assisted metathesis (σ-CAM). As some Ni(II) complexes were found in the triplet state, [39][40][41] geometry optimization, the H 2 simply dissociated away from the Ni. In the [NiFe] hydrogenase model study, Keith and Hall also reported that while the triplet state was possible for the Ni(II), H 2 binding to the high spin Ni was not found.…”
Section: B C-o Bond Hydrogenolysismentioning
confidence: 99%
“…Since early reports by Hodgkins in 1993 on bis­(pyridyl)­borates ( 1 ) and Jäkle in 2012 on tris­(pyridyl)­borates ( 2 ), there has been growing interest in poly­(pyridyl)­borates, which represent a new addition to the very popular scorpionate family. , These poly­(pyridyl)­borates have several attractive features over the better-known poly­(pyrazolyl)­borates as they have more thermally stable B–C linkages (compared to the relatively polar B–N linkages of the latter), four-substitutable positions on pyridyl groups ( vs three on pyrazolyl moieties), a closer proximity of the heterocyclic ring substituent to the metal site, and are believed to be better σ-donor ligands . Interestingly, despite several emerging applications, the reported poly­(pyridyl)­borates were limited to the parent systems based on unsubstituted pyridyl moieties ( e.g.…”
Section: Introductionmentioning
confidence: 99%